Desarrollo de la creatividad infantil para fortalecer el aprendizaje en niños de cuarto año de educación básica de la Unidad Educativa Emigdio Esparza Moreno Babahoyo 2022 - Murillo Vargas, Deysi María (2022)
The present research work was carried out in the Emigdio Esparza Moreno Educational Unitor, the same one that had as object of study to determine the incidence of the development of creativity in the strengthening of the learning of the children of 4th. year of EGB, the same that was developed through the identification of the causes that affect the development of creativity, as well as the contextualization on learning in such a way that they allow the development of methodological strategies that help the development of creativity in infants, which leads to the strengthening of their learning. The methodology of the project is descriptive with a quantitative approach since it processes numerical data obtained through field research through the application of techniques and instruments to the analysis unit, which in this case were the parents of the children and the teachers corresponding to the three parallels that the 4th has. EGB year. The information obtained allowed to establish the relationship of the two variables of studies, in which it is evident that among the factors that affect the development of creativity is the lack of methodological strategies on the part of teachers, adding to that that there are not enough materials for children to enhance their creativity influencing in such a way the strengthening of learning. In such a way that it is recommended that parents intervene in the development of creativity through motivation, since the child will feel more comfortable and at the same time develop creative thoughts that influence their skills.